The psychological well‐being of primary healthcare nurses during COVID‐19: A qualitative study. (18th June 2021) - Ashley, Christine; James, Sharon; Williams, Anna; Calma, Kaara; Mcinnes, Susan; Mursa, Ruth; Stephen, Catherine; Halcomb, Elizabeth
Abstract: Aim: To explore primary healthcare nurses' psychological well‐being related to the COVID‐19 pandemic. Design: Qualitative descriptive study. Methods: Semi‐structured interviews were conducted with 25 participants between June and August 2020 who indicated their willingness to participate in an interview following a national survey. Interviews were audio‐recorded and transcribed verbatim by professional transcribers. Data were analysed using thematic analysis. Results: The importance of professional and public support and acknowledgement of the nurses' role during the pandemic positively influenced feelings of being valued. The psychological impact of negative experiences increased anxiety and stress levels. Participants reported a range of self‐care strategies, including increased vigilance with infection control at home and work and attention to physical exercise and diet. Most participants remained positive about their roles and career decisions, although some indicated that the negative psychological impacts prompted re‐evaluation of their career. Conclusions: Primary healthcare nurses have been exposed to a range of personal and professional stressors during the pandemic that have impacted their psychological well‐being. Awareness of stressors and an understanding of what has helped and what has impacted well‐being are important in guiding future workplace support systems. Further work to explore the long‐term impact of these stressors and the effectiveness of coping strategies employed by primary healthcare nurses is warranted. Impact: Managers and professional organisations need to consider the personal and professional stressors that have impacted on primary healthcare nurses' psychological well‐being to promote health and well‐being among nurses following COVID‐19.